2019
DOI: 10.1186/s11658-019-0186-5
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-146a protects against myocardial ischaemia reperfusion injury by targeting Med1

Abstract: BackgroundMyocardial ischaemia reperfusion injury (MIRI) is a difficult problem in clinical practice, and it may involve various microRNAs. This study investigated the role that endogenous microRNA-146a plays in myocardial ischaemia reperfusion and explored the possible target genes.MethodsMIRI models were established in microRNA-146a deficient (KO) and wild type (WT) mice. MicroRNA-146a expression was evaluated in the myocardium of WT mice after reperfusion. The heart function, area of myocardium infarction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…SARS-CoV-2 infection in our cohort was also accompanied by the upregulation of some miRNAs known to orchestrate the innate and adaptive immune response: miR-146, miR-150, and miR-155. The role of miR-146 in attenuating inflammation and natural killer (NK) degranulation is widely recognised in several pathological conditions, [ 29 , 32 , 33 , 34 , 35 ], as well as in other viral infections [ 36 ]. It is, therefore, plausible that miR-146 rise in SIPW might contribute to the control of severe COVID-19 by limiting inflammatory damage of tissues, as well as by negatively regulating NK-dependent cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 infection in our cohort was also accompanied by the upregulation of some miRNAs known to orchestrate the innate and adaptive immune response: miR-146, miR-150, and miR-155. The role of miR-146 in attenuating inflammation and natural killer (NK) degranulation is widely recognised in several pathological conditions, [ 29 , 32 , 33 , 34 , 35 ], as well as in other viral infections [ 36 ]. It is, therefore, plausible that miR-146 rise in SIPW might contribute to the control of severe COVID-19 by limiting inflammatory damage of tissues, as well as by negatively regulating NK-dependent cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…However, OI could significantly diminish ROS accumulation and cell death induced by CCl4 in vitro ( Figures 4A,C,G ). Cleaved PARP and caspase 3 are important markers of cell apoptosis ( Zhang et al, 2019 ). In our study, cleaved PARP and caspase 3 were evaluated by immunoblot, and we found that CCl4 elevated them in NCTC 1469 cells, while OI treatment could decrease their expression.…”
Section: Discussionmentioning
confidence: 99%
“…73 Another study in miR-146a À/À mice revealed that miR-146a deficiency increased infarct size and apoptosis after I/R injury through the upregulation of 19 apoptosis-related genes such as mediator complex subunit 1 (Med1). 74 On the other hand, tyrosine kinases inhibitors agents such as sunitinib (SNT), beyond their beneficial effects on cancer, have shown adverse effects on the cardiovascular system. 75 Interestingly, Shen et al showed a significant downregulation of miR-146a in the myocardium of SNT-treated mice.…”
Section: Myocardial Infarctionmentioning
confidence: 99%